Cytokines and Soluble Receptors in Breast Milk as Enhancers of Oral Tolerance Development - Dawod, Bassel; Marshall, Jean S. (Frontiers in Immunology, 2019)
The postpartum period is an important window during which environmental factors can shape the life-long health of the infant. This time period often coincides with substantial milk consumption either in the form of breast milk or from cow’s milk sources, such as infant formulas. Although breast milk is the most beneficial source of nutrients for infants during the first six months after birth, its role in regulating food allergy development, through regulation of oral tolerance, is still controversial. Breast milk contains several factors that can impact mucosal immune function, including immune cells, antibodies, microbiota, oligosaccharides, cytokines, and soluble receptors. However, there is considerable variation in the assessed levels of cytokines and soluble receptors between studies and across the lactation period. Most of these cytokines and soluble receptors are absent, or only found in limited quantities, in commercial baby formulas. Differences in content of these pluripotent factors, which impact on both the mother and the neonate, could contribute to the controversy surrounding the role of breast milk regulating oral tolerance. This review highlights current knowledge about the importance of cytokines and soluble receptors in breast milk on the development of oral tolerance and tolerance-related disorders. Understanding the mechanisms by which such milk components might promote oral tolerance could aid in the development of improved strategies for allergy prevention.